Women's rights at work : a handbook of employment law - Clarke, Alison (Pluto Press, 2001)
Annotation "Women's Rights at Work" is a comprehensive guide that begins with the point when a woman finds work right through to the end when she finishes a job through dismissal or resignation. Starting from the premise that, while rights at work affect all workers, there are many issues that affect women workers in very specific ways. Topics covered include unfair dismissal, discrimination, harassment, maternity rights, and health and safety in the workplace. A British attorney specializing in women's employment rights, Alison Clark demystifies the subject and provides up-to-date reference guide to employment law for the non-specialist. Free from legalistic jargon, this book explains any unfamiliar terms in detail in order to make the law accessible to all women who want to assert their rights in the workplace
Keywords: Discrimination in employment -- Law and legislation -- Great Britain.; Sex discrimination against women -- Law and legislation -- Great Britain.; Women -- Employment -- Law and legislation -- Great Britain.; LAW -- Administrative Law & Regulatory Practice.; POLITICAL SCIENCE -- Human Rights.; Discrimination in employment -- Law and legislation; Sex discrimination against women -- Law and legislation; Women -- Employment -- Law and legislation; Great Britain